Beneficial effects of leaf extracts of lycoperscon esculentum on wound healing in rats (2015)
The study was aimed at determining the effects of the methanol extracts of the leaves of Lycoperscon esculentum on the wound healing in Wistar rats. Excisional wounds were inflicted on the upper dorsolateral trunk of normal saline (control) and tomato (Lycoperscon esculentum) leaf treated (TLT) adult rats and thereafter dressed four times daily for three days. Wound dimensions along two perpendicular axes were taken prior to dressings for the purpose of estimation of wound contraction rates. Granulation tissues were excised from five animals in each group and scar tissues obtained from the remaining animals. Fibroplasia and angiogenesis were evaluated histologically. Matched wound contraction rates were higher in the TLT group. Duration of healing was shorter in the TLT (19.80 ± 1.64 days) when compared with control (28.80 ± 4.55 days). Fibroblast counts of granulation tissue were 35.20 ± 17.53 (for TLT) and 24.00 ± 8.00 (for control), with respective angiogenesis counts of 12.60 ± 8.32 and 15.60 ± 5.77. Respective values for fibroblast and angiogenesis of the scar tissues in experimental and control groups were 18.40 ± 3.7 vs 20.80 ± 5.21; and 14.20 ± 1.92 vs 13.20 ± 1.64). Histological sections of the granulation and scar tissues revealed abundance of collagen and paucity of macrophages in the experimental group. Leaf extract of Lycoperscon esculentum promotes wound healing via bactericidal activity, rapid initiation and acceleration of wound contraction, increased fibroblast production and collagen synthesis